2017
DOI: 10.5901/jesr.2017.v7n2p153
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ Conflict Resolution Strategies and Teachers’ Job Effectiveness in Public Secondary Schools in Akwa Ibom State, Nigeria

Abstract: The thrust of this study was to investigate the relationship between Principals' conflict resolution strategies and teachers '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Edet et al [28] discovered that instructors' work performance significantly correlated with their use of conflict resolution methods in the classroom, including classroom management, upholding classroom discipline, and supervising students' academic activities. It has also been discovered that democratic, autocratic, and laissez-faire leadership styles all worked together to explain about 68.3 per cent of the variance in teachers' job performance [29] Generally, all the studies cited herein, have used different methodologies that suit the unique purpose of each study.…”
Section: Staff Managementmentioning
confidence: 99%
“…Edet et al [28] discovered that instructors' work performance significantly correlated with their use of conflict resolution methods in the classroom, including classroom management, upholding classroom discipline, and supervising students' academic activities. It has also been discovered that democratic, autocratic, and laissez-faire leadership styles all worked together to explain about 68.3 per cent of the variance in teachers' job performance [29] Generally, all the studies cited herein, have used different methodologies that suit the unique purpose of each study.…”
Section: Staff Managementmentioning
confidence: 99%
“…Dealing with conflict that escalates regularly among children can be an extremely frustrating experience (Ayas et al, 2010; Rubenstein, 2018). Studies have shown that children are likely to engage in up to eight peer conflicts per hour during a typical day (Edet et al, 2017; Hakvoort and Olsson, 2014; Johnson and Johnson, 2000). While this may seem excessive, most conflicts tend to be short in duration – around 30 seconds – and are often resolved by children themselves with little or no guidance from adults (Johnson and Johnson, 2000; Tobin, 2017; Tobin et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Although not all children’s conflicts require adult intervention, it is important for adults to teach children how to handle conflicts effectively at an early age (Bonache et al, 2016; Edet, et al, 2017). Studies indicate that violent behaviours are often learned early in kindergarten, if not before (Bonache et al, 2016; Stevahn et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations